2010
DOI: 10.1111/j.1365-2583.2010.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic analysis of the BmBLOS2 gene that governs the translucency of the larval integument of the silkworm, Bombyx mori

Abstract: The larval integument of the silkworm, Bombyx mori, is opaque because urate granules accumulate in the epidermis. Although the biosynthetic pathway of uric acid is well studied, little is known about how uric acid accumulates as urate granules in epidermal cells. In the distinct oily (od) mutant silkworm, the larval integument is translucent because of the inability to construct urate granules. Recently, we have found that the od mutant has a genomic deletion in the B. mori homologue of the human biogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…In the mutants oq (q-translucent) and og (giallo ascoli translucent), xanthine dehydrogenase activity is lost, and hence, the insect cannot synthesize uric acid (Komoto, 2002;Komoto et al, 2003). Fujii et al (2008Fujii et al ( , 2010 reported that the od (distinct translucent) gene encodes a Bombyx homolog of the BLOS2 subunit of the human biogenesis of lysosome-related organelles complex-1 (BLOC-1), which is related to a genetic disease, the HermanskyePudlak syndrome (Wei, 2006). Ito et al (2009) showed that a 25-bp insertional mutation in the BmVarp gene causes the ow (waxy translucent) phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…In the mutants oq (q-translucent) and og (giallo ascoli translucent), xanthine dehydrogenase activity is lost, and hence, the insect cannot synthesize uric acid (Komoto, 2002;Komoto et al, 2003). Fujii et al (2008Fujii et al ( , 2010 reported that the od (distinct translucent) gene encodes a Bombyx homolog of the BLOS2 subunit of the human biogenesis of lysosome-related organelles complex-1 (BLOC-1), which is related to a genetic disease, the HermanskyePudlak syndrome (Wei, 2006). Ito et al (2009) showed that a 25-bp insertional mutation in the BmVarp gene causes the ow (waxy translucent) phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The common phenotype of these mutants is translucent larval skin (22). Eight genes have been identified as causative genes in translucent larval skin mutants (23)(24)(25)(26)(27)(28)(29)(30)(31). These genes are involved in the synthesis or uptake of uric acid.…”
Section: Kaiko Functional Annotation Pipeline Is Useful For Screeningmentioning
confidence: 99%
“…In B. mori, ZFN-and TALENmediated gene mutagenesis targeting BmBLOS2 was reported [7,8]. BmBLOS2 is the homolog of the human biogenesis of lysosome-related organelles complex 1, subunit 2 gene, and is responsible for urate granule synthesis in B. mori larval epidermis [9]. When BmBLOS2 function is compromised, the larval integument is transformed from opaque to translucent, generating the oily skin phenotype (OSP).…”
mentioning
confidence: 99%